Type VI Secretion System in Pseudomonas aeruginosa: Secretion and Multimerization of VgrG Proteins - Hachani,A; Lossi,NS; Hamilton,A; Jones,C; Bleves,S; Albesa-Jove,D; Filloux,A (Journal of Biological Chemistry, 2011)
Pseudomonas aeruginosa is a Gram-negative bacterium causing chronic infections in cystic fibrosis patients. Such infections are associated with an active type VI secretion system (T6SS), which consists of about 15 conserved components, including the AAA+ ATPase, ClpV. The T6SS secretes two categories of proteins, VgrG and Hcp. Hcp is structurally similar to a phage tail tube component, whereas VgrG proteins show similarity to the puncturing device at the tip of the phage tube. In P. aeruginosa, three T6SSs are known. The expression of H1-T6SS genes is controlled by the RetS sensor. Here, 10 vgrG genes were identified in the PAO1 genome, among which three are co-regulated with H1-T6SS, namely vgrG1a/b/c. Whereas VgrG1a and VgrG1c were secreted in a ClpV1-dependent manner, secretion of VgrG1b was ClpV1-independent. We show that VgrG1a and VgrG1c form multimers, which confirmed the VgrG model predicting trimers similar to the tail spike. We demonstrate that Hcp1 secretion requires either VgrG1a or VgrG1c, which may act independently to puncture the bacterial envelope and give Hcp1 access to the surface. VgrG1b is not required for Hcp1 secretion. Thus, VgrG1b does not require H1-T6SS for secretion nor does H1-T6SS require VgrG1b for its function. Finally, we show that VgrG proteins are required for secretion of a genuine H1-T6SS substrate, Tse3. Our results demonstrate that VgrG proteins are not only secreted components but are essential for secretion of other T6SS substrates. Overall, we emphasize variability in behavior of three P. aeruginosa VgrGs, suggesting that, although very similar, distinct VgrGs achieve specific functions.